2012
DOI: 10.7314/apjcp.2012.13.4.1187
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Screening Status in Korea, 2011: Results from the Korean National Cancer Screening Survey

Abstract: This study was conducted to determine the use of screening for stomach, liver, colorectal, breast, and cervical cancers, which are included in the Korean National Cancer Screening Programme. In 2011 the National Cancer Centre in Korea conducted a nationwide, population-based, cross-sectional interview survey using multi-stage random sampling. Participants included 4,100 cancer-free men 40 years and over of age and women over 30 years of age. The lifetime screening rates for stomach, liver, colorectal, breast, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 8 publications
0
30
0
Order By: Relevance
“…Lack of access was also one of the most important barriers to breast cancer screening from women's point of view which consists of financial, geographical, and cultural access problems pointed out by most of the studies (Noroozi and Tahmasebi 2011;Park et al, 2011;Roder et al, 2013). Therefore making practical attempts to reduce screening costs and to insure these services, to increase women's geographical access by expanding centers and clinics providing these services in far and deprived locations and to provide these services by the primary care providers, and also to increase cultural access by service being provided by female practitioners or other female service providers, providing a private place in which the clients could feel convenience and safety and also attempts to produce culture of using these services, are recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of access was also one of the most important barriers to breast cancer screening from women's point of view which consists of financial, geographical, and cultural access problems pointed out by most of the studies (Noroozi and Tahmasebi 2011;Park et al, 2011;Roder et al, 2013). Therefore making practical attempts to reduce screening costs and to insure these services, to increase women's geographical access by expanding centers and clinics providing these services in far and deprived locations and to provide these services by the primary care providers, and also to increase cultural access by service being provided by female practitioners or other female service providers, providing a private place in which the clients could feel convenience and safety and also attempts to produce culture of using these services, are recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Since 1999, the National Cancer Screening Program (NCSP) in Korea has recommended biannual screening mammograms for females 40 years of age or older (1, 2). However, the outcome of breast cancer screening has been poor, showing the worst results among the five cancers included in the NCSP (3, 4).…”
Section: Introductionmentioning
confidence: 99%
“…As a complex and multifactorial process, the colorectal carcinogenesis is still not fully understood. Epidemiological studies have revealed that smoking, diets and other environmental risk factors play important roles in the development of CRC (Chan and Giovannucci, 2010;Park et al, 2011). However, only a small proportion of individuals exposed to the known risk factors develop CRC, while many cases develop CRC among individuals without those risk factors, which suggest genetic factors also play an important role in the colorectal carcinogenesis (Markowitz and Bertagnolli,metabolism, and thymidylate synthase (TYMS) catalyzes the conversion of deoxyuridine monophosphate (dUMP) to deoxythymidine monophosphate (dTMP) in the DNA synthesis by using 5, 10-methylenetetrahydrofolate as a methyl donor (Costi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%